ICT-BASED MATHEMATICS LEARNING MODULE: STUDENTS’ RESPONSES IN LEARNING PROCESS - Istikomah, Endang; Herlina, Sari (Jurnal PAJAR (Pendidikan dan Pengajaran), 2020)
The use of learning module aimed to help students study independently without or with the guidance of the lecturer. This module was made due to the lack of teaching materials as a learning guide that meets the needs of students in ICT-based Mathematics learning courses in the form of LKM, modules, or textbooks. This study aimed to find out and examine more in students' responses to the use of ICT-based Mathematics learning modules. This type of research was case study research. The subject of the study was the 2018/2019 even semester students in ICT-based Mathematics learning courses with 23 students. The instrument used was in the form of a student response questionnaire, comment sheets, and suggestions. Data collection techniques used Google Form. The data was processed using Microsoft Excel 2010. The results showed that students' responses to the ICT-based Mathematics learning module as a whole were positive with an average value in the material aspects, the module interest aspects, and in the module aspects respectively by 92.43%, 87%, and 93.16%. Thus, it can be concluded that the ICT-based Mathematics learning module can be implemented.